2018
DOI: 10.1080/15287394.2018.1502560
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Metabolism and Bioaccumulation of Sucralose In Adipose Tissue In The Rat

Abstract: The aim of this study was to (1) determine if the organochlorine artificial sweetener sucralose is metabolized in rat intestine with repeated dosing and (2) examine whether sucralose might bioaccumulate in rat adipose tissue. Sucralose was administered to 10 rats by gavage daily for 40 days at an average dosage of 80.4 mg/kg/day. The dosages were within the range utilized in historical toxicology studies submitted for regulatory approval in North America, Europe, and Asia. Feces and urine were collected indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
(34 reference statements)
0
19
0
3
Order By: Relevance
“…It is important to point out that even low sucralose concentration (1.5%), used in this study, showed similar effects than 10% sucrose. These results could be in part due to the fact that sucralose is metabolized in rats to compounds that are less polar and more lipophilic than the parent compound and persisted in adipose tissue two weeks after cessation of use [5]. L cells of the gut contain taste receptors that modulate GLP1 secretion in the gut and may play an important role in the development of obesity, diabetes, and changes in gut motility [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to point out that even low sucralose concentration (1.5%), used in this study, showed similar effects than 10% sucrose. These results could be in part due to the fact that sucralose is metabolized in rats to compounds that are less polar and more lipophilic than the parent compound and persisted in adipose tissue two weeks after cessation of use [5]. L cells of the gut contain taste receptors that modulate GLP1 secretion in the gut and may play an important role in the development of obesity, diabetes, and changes in gut motility [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the recent years, controversial results have been reported about the consumption of artificial sweeteners that have been associated with a greater risk of being overweight or obese [3]. Besides that, other studies have focused on other monosaccharides, particularly fructose [4], and few studies have focused on other natural complex sweeteners, such as honey, brown sugar, steviol glycosides, or the artificial sweetener sucralose [5]. In conditions of persistent intake of sweeteners, some taste receptors type 1 member 2 (T1R2) or member 3 (T1R3) are activated in tongue, intestine, and adipose tissue [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies in rats reveal that sucralose accumulates in adipose tissue and can be detected in adipocytes, urine, and feces 2 weeks after the rats stop receiving sucralose. [ 18 ] These findings and our present in vivo results in humans are particularly noteworthy because adipose tissue is central to whole body metabolism and adipose‐derived immune molecules, such as inflammatory cytokines, are highly expressed in obese individuals. [ 19 ] The contribution of inflammation to the pathogenesis of obesity‐associated cardiometabolic diseases, such as type 2 diabetes (T2D) and cardiovascular disease (CVD) is well‐established.…”
Section: Discussionmentioning
confidence: 64%
“…Sugar alcohols can also reach the colonic microbiota and act as prebiotics, with accompanying negative laxative effects [67], particularly in patients with inflammatory bowel syndrome (IBS). Since sucralose can deposit in fat tissue in an acelatyed version (see metabolism section), studies that have looked at the effect of sucralose with less than a week washout period could have to be revisited [68].…”
Section: Effect On Gut Biomementioning
confidence: 99%